Strategies in Language Education to Improve Science Student Understanding during Practicum in Laboratory: Review and Computational Bibliometric Analysis - Siti Pupu Fauziah; Irman Suherman; Mega Febriani Sya; Martin Roestamy; Amirullah Abduh; Asep Bayu Dani Nandiyanto (International Journal of Language Education, 2021)
The purpose of this study is to explain the development of language research in science learning which can improve students' understanding during practicums in the laboratory. This research also explores the factors that contribute to increasing student understanding and bibliometric analysis using the keywords "language", "practicum", "laboratory" and "science" from 2015 to 2021. There is also an explanation of curriculum development and the influence of language in science learning. The use of technology and laboratories is an important factor in improving student literacy and language. Student characteristics, motivation, teacher-student relationships, and student psychological conditions can all be concluded to be closely interconnected. Language is a determining factor in the success of science learning during practical work in the laboratory. Therefore, the language style used by the teacher during practicum in the laboratory should be as simple as possible to make students easy to understand. This paper also includes language barriers for students with special needs. The results of the bibliometric analysis show that the research trend on language in science learning is increasing. This paper can be used as material for consideration by readers in understanding the current conditions regarding the importance of language in science learning, especially practical learning in the laboratory.